Saw Files - Singh, Niranjan (Indian Forester, 1959)
Saw files playa very important role in the proper maintenance of all types of saws. Considerable damage is done to the saws as well as to the files by wrong choice of files for different jobs. This paper deals with certain basic facts regarding files and general instructions and recommendations for their use. (Collected from the book under reference).